Status of oxidative stress and characterization of APOB Gene Mutation in patients with Familial Hypercholesterolaemia / Nur Suhana Hamzan - Hamzan, Nur Suhana (2016)
Familial hypercholesterolaemia (FH) is an autosomal dominant genetic disorder characterized by high cholesterol concentration which increases oxidative stress and leads to coronary artery disease. Mutation in exon 26 and exon 29 of Apolipoprotein B (APOB) gene is one of the causes of FH. Oxidized low-density lipoprotein (oxLDL), F₂₋ isoprostanes (ISP) and Malondialdehyde (MDA) are established oxidative stress biomarker. The aim of this study is to investigate oxidative stress status and to identify genetic variants in APOB gene among FH patients and normocholesterolaemic (NC) subjects. Ninety-eight FH patients and 100 (age, gender and BMI matched) NC subjects were recruited in series of health screening programmes across the country. Fasting blood samples were analysed for serum oxLDL (ELISA), ISP (LCMS/MS) and MDA. Amplicons of exon 26 and 29 of APOB gene were screened by DNA sequencing. Ox-LDL, ISP and MDA concentrations were significantly higher in FH groups compared to NC (mean+SEM: 63.0+6.5 vs 25.5+1.2 (U/l), p<0.001); 749.7+74.0 vs 354.2+18.1 pg/ml, p<0.0001; 342.4+46.0 vs 162.7+13.5 nmol/g, p<0.0001). Ox-LDL shows significant correlation with glucose (p<0.05), TC (p<0.001), LDL-c (p<0.001) and HDL-c (p<0.01) in all subjects. High LDL-c was associated with high ox-LDL (p<0.001). LDL-c is an independent predictor for ox-LDL concentration (p<0.001). Known mutations were not found in all FH cases except for few insignificant genetic variations which are pThr2515Thr, p.Ile2716Ile, p.Pro2739Leu, p.Glu4181Lys, p.Arg4270Thr, p.Arg4297His and p.Ser4338Asn. These findings demonstrate that FH patients have higher oxidative stress concentration which suggests a greater risk of developing atherosclerosis. These results provide additional knowledge regarding FH in Malaysians.